Separating uncertainty from heterogeneity in life cycle earnings - Flavio Cunha; James J. Heckman; Salvador Navarro (Institute for Labour Market Policy Evaluation (IFAU), 2005)
This paper develops and applies a method for decomposing cross section variability of earnings into components that are forecastable at the time students decide to go to college (heterogeneity) and components that are unforecastable. About 60 % of variability in returns to schooling is forecastable. This has important implications for using measured variability to price risk and predict college attendance.
Keywords: C33; D84; I21; 330; earnings; unforecastable; forecastable; Lebenseinkommen; Lebenszyklus; Bildungsverhalten; Bildungsertrag; Schätzung; USA